10x+60=9x+90

Simple and best practice solution for 10x+60=9x+90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x+60=9x+90 equation:


Simplifying
10x + 60 = 9x + 90

Reorder the terms:
60 + 10x = 9x + 90

Reorder the terms:
60 + 10x = 90 + 9x

Solving
60 + 10x = 90 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
60 + 10x + -9x = 90 + 9x + -9x

Combine like terms: 10x + -9x = 1x
60 + 1x = 90 + 9x + -9x

Combine like terms: 9x + -9x = 0
60 + 1x = 90 + 0
60 + 1x = 90

Add '-60' to each side of the equation.
60 + -60 + 1x = 90 + -60

Combine like terms: 60 + -60 = 0
0 + 1x = 90 + -60
1x = 90 + -60

Combine like terms: 90 + -60 = 30
1x = 30

Divide each side by '1'.
x = 30

Simplifying
x = 30

See similar equations:

| 6x+5z=3+7y | | 700x-1/2x2 | | 12x+18=y | | 3x+62+70=180 | | 8g^2-2g-1=0 | | 5y(4y-4)+13y= | | 25x=15x+150 | | 3h+3v=5.25 | | e^9x+3=.36 | | 3h+3v=5 | | 2x+63+79=180 | | -2v^2+7v+8=0 | | (15z-20)=(14z+4) | | 10h+4v=10.00 | | 8x=-11+3y | | -3k^2-k+1=0 | | 12y=9x-30 | | y=-x^2+13x-30 | | -2f^2-8f-6=0 | | 3y+z=am-47 | | f(x)=4cos(7x+2)+4 | | 1/3r-4=2/3r | | 8n(2n+5)=25 | | 2y+1050=1504 | | 44.97=9g+3.84 | | 9x+7y=-16 | | 9x+7y=1-16 | | 3p^2+9p+4=0 | | 9-6/x=-3 | | -40=2(-5-3a) | | s^2-7s-3=0 | | 9g^2-3g-2=0 |

Equations solver categories